Growth and development and trends in overweight and obesity among 7–12 years old Hmong children in China: an analysis of eight successive national surveys from 1985 to 2019 - Pan, Qi; Li, Yuyu; Chen, Xiaolong; Dai, Xinyi; Zhang, Xueliang; Tu, Chunjing (Frontiers in Public Health, 2024)
Background To explore the dynamic changes and trends in the body shape of Hmong children aged 7–12 years from 1985 to 2019, and to predict them, to provide a reference for the physical health level of Hmong children. Methods The body shape data of Hmong children aged 7–12 years old from the Chinese National Survey on Students’ Constitution and Health (CNSSCH) in 1985, 1991, 1995, 2000, 2005, 2010, 2014, and 2019 were used for longitudinal comparative analysis, and the grey GM(1,1) model was established based on this as a time series. Forecast the future development trend in 2025 and 2030. Results 1) From 1985 to 2019, all indicators of body shape of Hmong primary school students showed an upward trend, the increase in height (FBoys = 3.91, p > 0.05; FGirls = 3.91, p > 0.05), weight (FBoys = 8.04, p < 0.01; FGirls = 6.36, p < 0.05) and BMI (FBoys = 19.15, p < 0.01; FGirls = 10.24, p < 0.01) increased with age, rate of growth: Weight > BMI > Height, girls grow faster than boys; 2) The prevalence of overweight and obesity increased year by year, from 5.2 and 1.2% in 1991 to 12.4% (χ2linear trend = 3.89, p < 0.05) and 8.7% (χ2linear trend = 3.98, p < 0.05) in 2014, respectively, showing a significant growth trend, especially after 2000, overweight and obesity have entered a stage of rapid growth; 3) The forecast results show that the height, weight and BMI will continue to increase in 2025 and 2030, but the growth rate will decrease, the increase of weight and BMI is greater than the height, overweight and obesity are still expected to increase rapidly. Conclusion The growth and development level of Hmong elementary children continues to increase, and the prevalence of overweight and obesity is increasing year by year, requiring early prevention and intervention to promote the healthy development of physical fitness of Hmong, as well as other ethnic minority students.